Use of a thrombopoietin receptor agonist in von Willebrand disease type 2B (p.V1316M) with severe thrombocytopenia and intracranial hemorrhage. (4th July 2017) - Espitia, O.; Ternisien, C.; Agard, C.; Boisseau, P.; Denis, C. V.; Fouassier, M.
Abstract: We present here a 63-year old woman with a long history of immune thrombocytopenia. She was hospitalized for a traumatic intracranial hemorrhage with thrombocytopenia. Following inefficient treatment of four platelet transfusions, immunoglobulins, and corticosteroids, we initiated treatment with a thrombopoietin (TPO) receptor agonist (eltrombopag 25 mg/d) with a good efficacy. Her mother and sister also had chronic thrombocytopenia. Clinical history, hemostasis results, and gene analysis revealed von Willebrand disease (VWD) type 2B with the mutation (c.3946G>A; p.V1316M), which combines a von Willebrand factor defect with severe thrombocytopenia, as well as a thrombocytopathy. The efficacy of TPO receptor agonists appears to counterbalance, at least to some extent, the thrombocytopathy associated with this mutation. As such, the use of TPO receptor agonists could represent an alternative therapeutic approach in cases of VWD type 2B with severe thrombocytopenia.